Determinants Of Capital Structure On Property And Real Estate Companies Listed On The Indonesia Stock Exchange For The Period Of 2015-2020 - Nabila Nurul Aini; Suherman Suherman; Umi Mardiyati (LPPPIPublishing, 2022)
This study aims to determine the effect of profitability, firm size, firm age, non-debt tax shield, tangibility, growth opportunities, and earnings volatility on the capital structure of the property and real estate sector companies listed on the Indonesia Stock Exchange for the period of 2015-2020. Independent variables used in this study are profitability, firm size, firm age, non-debt tax shield, tangibility, growth opportunities, and earnings volatility. The Dependent variable used is the capital structure (DER and DAR). This study also uses a control variable, namely institutional ownership. The sampling technique used in this study is purposive sampling with as many as 43 property and real estate companies that matched the sample criteria in the study. This study uses panel data regression analysis techniques using the Common Effect Model (CEM) and Random Effect Model (REM) approaches. The results of this study indicate that profitability, firm age, non-debt tax shield, growth opportunities, and earnings volatility have a negative and insignificant effect on capital structure (DER), while firm size has a positive and significant effect on capital structure (DER). The results of the robustness check with the Debt to Assets Ratio as a proxy for capital structure show that profitability, firm size, firm age, and growth opportunities have robust results, while non-debt tax shields, tangibility, and earnings volatility have not robust results. Therefore this research supports the trade-off theory, pecking order theory, and signaling theory.